Effect of Particle Size and Temperature on Pyrolysis of Palm Kernel Shell - Zaman, Khairunnisa Kamarul; Balasundram, Vekes; Ibrahim, Norazana; Samsudin, Mohammad Dinie Muhaimin; Kasmani, Rafiziana Md.; Abd Hamid, Mohd. Kamaruddin; Hasbullah, Hasrinah (International Journal of Engineering and Technology, 2018)
Pyrolysis is a viable solution to curb the issue of growing lignocellulosic waste in the world through conversion to potential biofuel and bio-based chemicals. This study focused on the effect of biomass particle size on the feedstock characterisation, biomass ash content, thermal behaviour and pyrolysis products yield. The particle size ranges studied were
Keywords: Ash content; palm kernel shell; particle size; pyrolysis; temperature